"Se il partito più caritatevole non sarebbe di 'chiudere' l'Africa?" Stereotipi, esotismo e discorso coloniale nel resoconto africano di Emilio Cecchi. (2nd October 2021) - Bedin, Cristiano
ABSTRACT: The article aims to analyse Appunti per un periplo dell'Africa (1954), a travel book written by Emilio Cecchi that narrates the writer's impressions and experiences in some Portuguese African colonies. The text is influenced by fascist propaganda, linked to imperialism, and shows the tendency to present African populations as the object of colonization. We consider the various stereotypes and images that Cecchi uses in the representation of the colonized people of the Portuguese territories in Africa, in particular in discourses focused on race, women, dance and the colonial system. It turns out that Cecchi's work is fully inserted into the ideological context of the early twentieth century, reaffirming a colonial discourse that supports the primacy of the civilized European over the primitive African and giving into the fascination for the exotic, typical of colonial literature.